Suspected Adverse Drug Reactions in Pediatric Cancer Patients in China: An Analysis of Henan Province Spontaneous Reporting System Database - Jiao, Zhiming; Feng, Zhanchun; Yan, Ziqi; Zhang, Jinwen; Li, Gang; Wang, Ganyi; Wang, Qianyu; Feng, Da (Frontiers in Oncology, 2021)
Introduction Adverse drug reactions (ADRs) in pediatric cancer patients have not yet received due attention in the world. Antineoplastic drugs are frequently related to ADRs. Few studies focus on the ADR and the intervention measures in pediatric cancer patients. Methods ADR reports submitted to Henan Adverse Drug Reaction Monitoring Center from 2016 to 2020 for individuals aged from birth to 17 years (including 17 years) were included. Data were analyzed with respect to gender, age, disease types, past history of ADR, occurrence time of ADR, polypharmacy, route of administration, off-label drug use, name of suspected drugs per ADR report, and severity of ADR reports. Results A total of 431 ADR reports related to antineoplastic drugs in pediatric patients were collected, 31.55% were serious ADRs (SADRs). The median age of patients was six years (inter quartile range, IQR: 3-11), the age groups with higher reporting rates were concentrated in 1-3-year-olds (130). Past history of ADR, occurrence time of ADR and polypharmacy were statistically associated with SADR. Myelosuppression was the most frequent ADR (15.55%), cytarabine was the most frequent drug (26.22%). The signal mining method produced 14 signals, three signals were off-label ADRs. Conclusions This study described the characteristics of ADRs in pediatric cancer patients. By conducting signal mining method, three off-label ADRs need further study. We should pay more attention to these ADRs and develop relative management strategies. More researches are needed to achieve a better understanding of the characteristics of ADRs in pediatric cancer patients of China.